INOVASI PEMBELAJARAN BERMAKNA UNTUK MENINGKATKAN KREATIVITAS SISWA DI SMP UNISMUH MAKASSAR - Ulviani, Maria; Rimang, Siti Suwadah; Kemala, Rosmalina (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Makassar, 2025)
Meaningful learning is an important approach to improving the quality of student learning, particularly in developing creativity, a requirement of 21st-century learning. This study aims to analyze the effectiveness of meaningful learning innovations in enhancing the creativity of junior high school students at Unismuh Makassar. The study used a classroom action research (CAR) method implemented in two cycles. The subjects were 30 eighth-grade students. Data were obtained through observation, creativity tests, and documentation, then analyzed descriptively using qualitative and quantitative methods. The results showed a significant increase in creativity indicators, including originality, fluency, flexibility, and elaboration. In the first cycle, the average student creativity was in the moderate category, while in the second cycle, it increased to the high category. Thus, meaningful learning innovations have been proven to create an active, contextual learning atmosphere and encourage students to be more innovative. The conclusion of this study confirms that meaningful learning is an effective strategy for enhancing junior high school students' creativity and can serve as a practical reference for teachers in developing innovative learning in the classroom.